Coverage and Priority of Crime Issues in Newspapers: A Study of National Dailies - Magar, Rojina Ale; KC, Buddhi Bahadur; Ghimire, Prakash (Journal of Kapan Multiple Campus, 2025)
This article is focused on the study of coverage and priority of crime issues in Nepali daily newspapers, which is done by analyzing the content during a one-month period of time, representing three daily newspapers (Kantipur, Himalayan Times, and Gorkhapatra). The objective of this study is to analyze the media coverage on crime reporting in Nepali Daily Newspapers. This study is mainly based on a descriptive research design. For the descriptive information, statistical tools like percentage, frequency, pie-chart, bar diagram, etc., were used as per the nature of the variables. For KIIs, interviews are taken with the reporters, editors, police investigators, and experts. The content analysis of this study reveals that among the three National Daily Newspapers, Gorkhapatra has given less priority than Kantipur and Himalayan Times on the publication of crime-related news on the front page. Among 276 crime-related news published on three daily newspapers, 141 (51.1%) were personal crime news, 55 (19.9%) were property crime news, 24 (8.7%) were inchoate crime news, 49 (17.8%) were statutory crime news, and interview and articles related to crime was published 7 (2.5%) times in November. The maximum of personal crime news published in the newspaper was homicide/murder, rape/sexual assault, body missing, etc. The maximum of property crime news is bribery and robbery, most of the inchoate news is related to conspiracy, and most of the statutory crimes were gambling, illegal weapons, bombs, smuggling, drug-related crime, etc. Study shows that daily newspapers are published event-based and incident crime issues rather than investigation-based issues; the follow-up of successful crime news is also unsatisfactory. Reporters are found to be more dependent upon press statements and police sources. However, the study reveals that print media are also playing a positive role in the publicity of hidden issues, crime, etc.